Association Study between rs10486567, rs13149290, rs1545985 and rs6983267 with Incidence of Prostate Adenocarcinoma Among Iranians - Allahverdi, Mina; Angaji, Seyed A.; Beikzadeh, Behnaz; Roudi, Raheleh (Current Pharmacogenomics and Personalized Medicine, 2024)
Introduction: Prostate cancer is the second most frequent malignancy after lung cancer among men, accounting for 7% of new cancers diagnosed around the world (15% in developed regions). This disease has become more prevalent in Iran over the past few decades, moving up the rankings from 13th in 1986 to 4th in 2005 and finally reaching third place in a recent study in 2016. The purpose of this study is to investigate the association of rs10486567, rs13149290, rs6983267, and rs1545985 with prostate cancer predisposition in the Iranian population. Due to the genetic heterogeneity, each of the SNP should be studied separately in various communities. Material and Methods: This study was conducted as a case-control study on 200 patients referred to Hashminejad Hospital in Tehran. 103 men with prostate adenocarcinoma were selected as case, and 97 men with benign prostatic hyperplasia (BPH) were selected as control. In this research, according to FAVORGENE-Taiwan extraction kit instructions, genomic DNA was extracted from peripheral blood lymphocytes Tetra-primer ARMS-PCR method was used for SNP genotyping. Results: The significance level at the first stage was p-value≤0.4. rs10486567 (p-value = 0.802) and rs6983267 (p-value = 0.684). Based on the additive and multiplicative genetic model, no association of these polymorphisms with prostate adenocarcinoma was observed. As a result, rs10486567 and rs6983267 were removed at this stage. rs13149290 (p-value=0.4) and rs1545985 (p-value=0.4) at this stage were selected for the next stage. At the second stage rs13149290 (p-value=0.043) showed a significant difference in the comparison between the two groups, but this difference was not observed in relation to rs1545985 (p-value=0.392) rs1545985 was not associated with prostate adenocarcinoma in the additive genetic model. According to P=0.013 and OR (95% CI) =3.837 (1.306-11.268), rs13149290 polymorphism is associated with prostate adenocarcinoma in the additive genetic model (TT vs. CC). Conclusion: As a result of this study, it was observed that rs13149290 is associated with prostate cancer in the Iranian population. Also this polymorphism is associated with Gleason score=7 and PSA ≤4. Prostate cancer as an exposure effect is heterogeneous between different PSA levels. It is suggested that this polymorphism be investigated in a larger population and in each ethnic group separately.
Keywords: prostate adenocarcinoma